2022
DOI: 10.3390/vaccines10030405
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Nanovaccines for SARS-CoV-2 to Address COVID-19

Abstract: COVID-19 is still prevalent around the globe. Although some SARS-CoV-2 vaccines have been distributed to the population, the shortcomings of vaccines and the continuous emergence of SARS-CoV-2 mutant virus strains are a cause for concern. Thus, it is vital to continue to improve vaccines and vaccine delivery methods. One option is nasal vaccination, which is more convenient than injections and does not require a syringe. Additionally, stronger mucosal immunity is produced under nasal vaccination. The easy acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 116 publications
(120 reference statements)
0
15
0
Order By: Relevance
“…Intranasal vaccination against respiratory and gastrointestinal pathogens offers many practical and theoretical advantages [ 8 ]. The vaccine is delivered directly to the mucosal surface, and this should enhance mucosal cellular and humoral immune responses [ 9 , 10 ]. Individuals with direct experience with intranasal vaccination tend to favor it over needle injection, as it is considered less painful and less intrusive to the body, equally effective, and associated with fewer side effects [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intranasal vaccination against respiratory and gastrointestinal pathogens offers many practical and theoretical advantages [ 8 ]. The vaccine is delivered directly to the mucosal surface, and this should enhance mucosal cellular and humoral immune responses [ 9 , 10 ]. Individuals with direct experience with intranasal vaccination tend to favor it over needle injection, as it is considered less painful and less intrusive to the body, equally effective, and associated with fewer side effects [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies present in the mucosal layer may neutralize protein subunit vaccines. Furthermore, the proteases found in the nose can also diminish their immunogenicity [ 245 ]. Novel vaccine delivery systems are necessary for nasal vaccination.…”
Section: Needle-free Particulate Delivery Systems Of Covid-19 Vaccinementioning
confidence: 99%
“…Novel vaccine delivery systems are necessary for nasal vaccination. NPs have greater controllability and safety as an alternative to biological vectors [ 245 ]. PLGA NPs, liposomes, and NP assemblies have the ability to stop the neutralization of antigens and improve cellular uptake.…”
Section: Needle-free Particulate Delivery Systems Of Covid-19 Vaccinementioning
confidence: 99%
“…Studies on COVID-19 vaccine and detection assay development will likely continue to be reported, and the generation of new vaccines and detection assays, particularly those for new and severe SARS-CoV-2 variants (e.g., Delta [48] and Omicron [49] ), will probably be emphasized. For example, the development of nasal-delivered nanovaccines [50] has gained much attention, and frugal diagnostic approaches, like RNA-extraction-free nanotechnology, for SARS-CoV-2 detection [51] also inspired considerable research interest.…”
Section: Future Trendsmentioning
confidence: 99%